2016
DOI: 10.2147/ott.s115221
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between epidermal growth factor receptor tyrosine kinase inhibitor efficacy and circulating tumor cell levels in patients with advanced non-small cell lung cancer

Abstract: ObjectiveThe aim of this study was to investigate the correlation between the efficacy of epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) and circulating tumor cell (CTC) levels in patients with advanced non-small cell lung cancer (NSCLC). The efficacy of EGFR-TKIs in reducing CTC counts in patients with advanced NSCLC was studied.Patients and methodsA total of 66 patients with advanced NSCLC were enrolled and divided into two groups (those with high CTC counts and those with low CTC coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…He et al . reported that a higher baseline CTC count was significantly associated with inferior PFS (5.6 vs. 11.5 months; P = 0.005) and OS (18.3 vs. 22.8 months; P = 0.010) rates in advanced NSCLC patients with EGFR mutations . These findings in EGFR ‐mutated NSCLC patients correspond to the results of our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…He et al . reported that a higher baseline CTC count was significantly associated with inferior PFS (5.6 vs. 11.5 months; P = 0.005) and OS (18.3 vs. 22.8 months; P = 0.010) rates in advanced NSCLC patients with EGFR mutations . These findings in EGFR ‐mutated NSCLC patients correspond to the results of our study.…”
Section: Discussionsupporting
confidence: 90%
“…To our knowledge, this study provides the first complete evidence of the prognostic value of baseline CTC counts for predicting PFS and OS rates in patients with positive EGFR / ALK. To date few reports have investigated the prognostic significance of CTCs in EGFR ‐mutated or ALK ‐rearranged NSCLCs . Yang et al .…”
Section: Discussionmentioning
confidence: 99%
“…CTC were assessed by flow cytometry in 66 EGFR mutant advanced NSCLC patients (46). Patients were divided in two groups (high CTC count vs. low CTC count) based on the median CTC count of 68.5.…”
Section: Prognostic and Predictive Value Of Ctc In Advanced Nsclcmentioning
confidence: 99%
“…CTCs are thought to be metastatic cells from the solid tumor site and are one of the avenues for metastasis from the primary tumor site to distant tissues, thus CTCs are associated with tumor progression and patient prognosis . Moreover, because it is thought that CTCs reflect characteristics of the primary solid tumor such as genetic alterations and expression of therapeutic targets, CTCs may be useful for estimating established biomarkers that can monitor response to treatment and the presence or lack of tumor‐specific therapeutic targets . Therefore, the detection and analysis of CTCs could be a minimally invasive diagnostic procedure for repetitive monitoring and deciding on therapeutic strategy.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Moreover, because it is thought that CTCs reflect characteristics of the primary solid tumor such as genetic alterations and expression of therapeutic targets, 8,9 CTCs may be useful for estimating established biomarkers that can monitor response to treatment and the presence or lack of tumor-specific therapeutic targets. [10][11][12] Therefore, the detection and analysis of CTCs could be a minimally invasive diagnostic procedure for repetitive monitoring and deciding on therapeutic strategy. CellSearch is the only FDA-approved CTC enumeration platform and has demonstrated the clinical utility of CTCs in a several cancers, 7,13,14 however, their utility in non-small cell lung cancer (NSCLC) has been limited by the low expression of EpCAM in CTCs derived from NSCLC patients.…”
Section: Introductionmentioning
confidence: 99%